Reducing uncertainties about the effects of chemoradiotherapy for cervical cancer: A systematic review and meta-analysis of individual patient data from 18 randomized trials - Claire Vale (2018)
Background: After a 1999 National Cancer Institute (NCI) clinical alert was issued, chemoradiotherapy has become widely used in treating women with cervical cancer. Two subsequent systematic reviews found that interpretation of the benefits was complicated, and some important clinical questions were unanswered. Patients and Methods: We initiated a meta-analysis seeking updated individual patient data from all randomized trials to assess the effect of chemoradiotherapy on all outcomes. We prespecified analyses to investigate whether the effect of chemoradiotherapy differed by trial or patient characteristics. Results: On the basis of 13 trials that compared chemoradiotherapy versus the same radiotherapy, there was a 6% improvement in 5-year survival with chemoradiotherapy (hazard ratio [HR] = 0.81, P < .001). A larger survival benefit was seen for the two trials in which chemotherapy was administered after chemoradiotherapy. There was a significant survival benefit for both the group of trials that used platinum-based (HR = 0.83, P = .017) and non-platinum-based (HR = 0.77, P = .009) chemoradiotherapy, but no evidence of a difference in the size of the benefit by radiotherapy or chemotherapy dose or scheduling was seen. Chemoradiotherapy also reduced local and distant recurrence and progression and improved disease-free survival. There was a suggestion of a difference in the size of the survival benefit with tumor stage, but not across other patient subgroups. Acute hematologic and GI toxicity was increased with chemoradiotherapy, but data were too sparse for an analysis of late toxicity. Conclusion: These results endorse the recommendations of the NCI alert, but also demonstrate their applicability to all women and a benefit of non-platinum-based chemoradiotherapy. Furthermore, although these results suggest an additional benefit from adjuvant chemotherapy, this requires testing in randomized trials. © 2008 by American Society of Clinical Oncology.